(untitled) (ENTHYMEMA, 2016)
Il “nuovo realismo” filosofico si fonda su presupposti estranei, se non apertamente ostili, rispetto alla letteratura, e quindi ha poco a che fare con il realismo letterario. Quest’ultimo è invece interpretato e supportato con efficacia dall’ermeneutica, contro cui il nuovo realismo ha acceso una dura polemica. The philosophical movement known as “New Realism” is based on assumptions which are alien, if not plainly hostile, to literature. Therefore it has little to share with literary realism, which on the contrary is effectively explained and supported by Hermeneutics, i.e. by the frequent polemic target of New Realism.